The Relationship Between Tendency to Computer Games and the Mental Health of Junior High School Students of Shahr-e Kord, Iran - Zahra Karimi; Elahe Tavassoli; Akbar Babaei Heydarabadi (Shahrekord University of Medical Sciences, 2019)
Background and aims: Given that computer games have positive and negative functions and may affect the mental health of individuals, the present research aimed to study the relationship between the tendency to playing computer games and the mental health of junior high school students in Shahr-e Kord. Methods: The current cross-sectional descriptive-analytical study was conducted on 245 boy and girl junior high school students of Shahr-e Kord in 2016. The participants were selected using a random cluster sampling method. The required data were collected using questionnaires of demographic variables, the standard 28-item General Health Questionnaire, and an author-made questionnaire on the tendency to computer games. Finally, the data were statistically analyzed using descriptive and analytic tests in SPSS-18. Participation in the study was voluntary. Results: The results showed that 31.8% of the students aged 14 years old. In addition, the tendency to computer games was higher in girls (0.027) and their level of mental health was lower compared to boys (P=0.032). There was a significant relationship between the tendency to computer games and the age of the students (P=0.023). Eventually, age (P=0.025) and gender (P=0.09) represented a significant relationship with the mental health of the students. Conclusion: Based on the low level of mental health in girls, it is necessary to pay special attention to the symptoms of depression and anxiety and social functions in adolescents, control the time spent on playing the computer games, plan carefully for their leisure time, direct adolescents toward reading books, and promote their health using educational patterns.